2010
DOI: 10.1111/j.1365-2052.2010.02019.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of swine leucocyte antigen class II genes in outbred pig populations

Abstract: The highly polymorphic swine leucocyte antigen (SLA) genes are among the most important determinants of swine immune responses to disease and vaccines. Accurate and effective SLA genotyping methods are required to understand how SLA gene polymorphisms affect immunity, especially in outbred pigs with diverse genetic backgrounds. In this study, we present a simple and rapid molecular-based typing system for characterizing SLA class II alleles of the DRB1, DQB1 and DQA loci. This system utilizes a set of 47 seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 27 publications
4
74
0
Order By: Relevance
“…Exon 3 of SLA-DQA encodes the external cellular a2 domain, in which the a2 and b2 domains intertwine and form intra-chain disulfide bonds to maintain DQA molecular structure (Ho, 2006). In the present study, we confirmed that a statistical association exists between the genotypes of exon 3 and diarrhea susceptibility and resistance.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Exon 3 of SLA-DQA encodes the external cellular a2 domain, in which the a2 and b2 domains intertwine and form intra-chain disulfide bonds to maintain DQA molecular structure (Ho, 2006). In the present study, we confirmed that a statistical association exists between the genotypes of exon 3 and diarrhea susceptibility and resistance.…”
Section: Discussionsupporting
confidence: 83%
“…SLA-DQA is a SLA class II gene that is expressed at the mRNA and protein levels, is approximately 5.5 kb in length, and encodes a polypeptide of 255 amino acid residues (Ho, 2006). This gene contains four exons and three introns: exon 1 encodes a signal peptide, exons 2 and 3 encode corresponding external cellular a1 and a2 domains, and exon 4 encodes both the transmembrane and cytoplasmic domains.…”
Section: Introductionmentioning
confidence: 99%
“…The SLA-DQA gene plays important roles in immune responsiveness and disease resistance (susceptibility) (Gautschi and Gaillard, 1990;Ho et al, 2010). Variation in genes may affect immune responses to pathogens, leading to variation in disease susceptibility (Racioppi et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The information of 47 primer pairs for SLA class I alleles (SLA-1, SLA-3, SLA-2), 47 primer pairs for SLA class II alleles (DRB1, DQB1, DQA) and positive control primers for the porcine α-actin (ACTA1 gene) was already obtained from description published by Ho et al (2009aHo et al ( , 2010a. The PCR amplification was carried out under the condition of denaturation for 10 min at 94 followed by 35 cycles of 96 for 15 s, 65 for 20 s and 72 for 20 s, with final extension of 3 min at 72 , then holding at 4 using a 96-well MJ Research PTC-200 thermal cycler (Bio-Rad, USA).…”
Section: Sla Genotyping By Pcr-ssp Methodsmentioning
confidence: 99%
“…On the other hand, SLA class III genes having wide range of functions and some of them are related to the complement cascade (Naziruddin et al, 1998). In 2002, SLA Nomenclature Committee of the International Society for Animal Genetics (ISAG) has been established for the systematic nomenclature of the class I and class II SLA alleles (Smith et al, 2005a;Smith et al, 2005b;Ho et al, 2009a;Ho et al, 2009b;Ho et al, 2010a). The recent updates of SLA alleles can also be found in Immunopolymorphism Database-Major Histocompatibility Complex (IPD-MHC) website (http://www.ebi.ac.…”
Section: Introductionmentioning
confidence: 99%